Do Organizational Socialization Tactics Influence Newcomer Embeddedness and Turnover? - Allen, David G. (Journal of management, 2006)
The author proposes that socialization tactics influence newcomer turnover by embedding newcomers more extensively into the organization. Hypotheses are tested with a sample of newcomers in a large financial services organization. Results reveal that socialization tactics enable organizations to actively embed new employees; collective, fixed, and investiture tactics were positively related to on-the-job embeddedness. Results also indicate that on-the-job embeddedness is negatively related to turnover and mediates relationships between some socialization tactics and turnover.